How can acute mountain sickness be quantified at moderate altitude? - Roeggla, G (1996)
Reports of acute mountain sickness (AMS) at moderate altitude show a wide variability, possibly because of different investigation methods. The aim of our study was to investigate the impact of investigation methods on AMS incidence. Hackett's established AMS score (a structured interview and physical examination), the new Lake Louise AMS score (a self-reported questionnaire) and oxygen saturation were determined in 99 alpinists after ascent to 2.94 km altitude. AMS incidence was 8% in Hackett's AMS score and 25% in the Lake Louise AMS score. Oxygen saturation correlated inversely with Hackett's AMS score with no significant correlation with the Lake Louise AMS score. At moderate altitude, the new Lake Louise AMS score overestimates AMS incidence considerably. Hackett's AMS score remains the gold standard for evaluating AMS incidence.